Agrobacterium?mediated Genetic Transformation of Two Varieties of Brassica juncea (L.) Using Marker Genes (Plant Tissue Culture and Biotechnology, 2016)
Protocol for Agrobacterium?mediated genetic transformation using hypocotyl and cotyledonary leaf with petiole from two local varieties of Brassica juncea was established by optimizing various factors influencing transformation. GUS histochemical assay revealed that the cotyledonary leaf with petiole and hypocotyl explants had positive interaction with the Agrobacterium strain LBA4404 containing the binary plasmid pBI121 which has marker genes like, GUS and nptII. Maximum transformation was obtained with bacterial suspension having an optical density of 0.8 at 600 nm, 30 min of incubation and 72 hours of co?cultivation. The transient and stable integration of the marker genes were confirmed through histochemical GUS assay, as well as PCR analysis.Plant Tissue Cult. & Biotech. 26(1): 55-65, 2016 (June)